A landcsape of enterprise resource planning implementation - Hassan, Marina; A. Jabar, Marzanah (UUM College of Arts and Sciences, Universiti Utara Malaysia, 2013)
Enterprise Resource Planning (ERP) system is a business management system that comprises enterprise business elements in information system. The use of ERP software applications is to improve the performance of organizations‘ resource planning, management control and operational control. Literature search related to ERP reveal 297 papers. After further reading done, 77 papers were identified as a key paper for the topics chosen. In understanding the landscape of ERP in organization, we analyze 16 ERP implementation papers from the literature year 2000 to 2012. We do details search on theoretical foundation of ERP growing in the market together with ERP best complement lifecycle to be implement. Based on ERP literature analysis of ERP implementation comparison a conceptual conclusion will be made at the end of this paper. A conceptual model of ERP lifecycle will be developed to understand the stages of how to choose a quality ERP software based on organization objective. This paper will be guidelines for organization to start implement ERP software in running their business more effective and efficiency in facing the globalizations.